Efektifitas Pengadaan Barang dan Jasa Secara Elektronik (E-Procurement) pada Bagian Layanan Pengadaan Barang dan Jasa Setda Kabupaten Mamberamo Tengah - Darlin Sukin Simanjuntak; Yosephina Ohoiwutun; Muhlis Hafel (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to describe and analyze the Effectiveness of Electronic Procurement of Goods and Services (E-Procurement) at BPBJ SETDA Central Mamberamo Regency, to describe and analyze what factors support and hinder the Effectiveness of Electronic Procurement of Goods and Services (E-Procurement). Procurement) at BPBJ Central Mamberamo Regency. The method used in this research is a qualitative research method with data collection techniques namely interviews, observation, and documentation. The results of the study show that achieving goals in BPBJ services in Central Mamberamo Regency has been effective as seen from the achievement of work targets that have been achieved. So that the process of using the e-Procurement application has been maximized by all users and the auction process runs smoothly, integration in the Central Mamberamo Regency Regional Secretariat's BPBJ services has been carried out well, where the socialization carried out by BPBJ is direct and routinely carried out periodically, Central Mamberamo Regency Regional Secretariat's BPBJ has not yet fulfill aspects of good adaptation, because it is still constrained by inadequate internet networks and human resources. Supporting factors include increasing human resource capabilities, intensive training, and introducing a program to targets and factors. The obstacles to using e-procurement are PBJ Regional Secretariat of Central Mamberamo Regency, namely: Inadequate internet network, Medan in the Kobakma area which is difficult to reach, and virus problems which can interfere with the running of the application. Conclusion, Effectiveness The effective use of electronic procurement of goods and services (e-procurement) in the goods and services procurement services section of SETDA Central Mamberamo Regency is divided into 3 aspectsKeywords: E-Procurement, Human Resources, Procurement of Goods and Services